Transparency in Non-Tariff Measures: An International Comparison - Lili Yan Ing; Janine Walz; Olivier Cadot (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
We construct an index of NTM transparency based on notifications to the WTO under the SPS and TBT agreements, the existence of a trade portal giving ready access to trade-relevant regulations, the existence of NTM data collected under the MAST classification, and the results of an experiment conducted between 2015 and 2016 where we asked for specific regulations concerning the import of a particular product on behalf of a private company. The resulting country ranking shows that OECD countries are, by and large, the most transparent, but also shows that ASEAN countries score well compared to other developing countries. Keywords: International trade, Non-tariff measures, transparency, governance, index, ranking
Keywords: F12; F13; F14; F15; F6; 330; International trade; Non-tariff measures; transparency; governance; index; ranking